Family-Four Aldehyde Dehydrogenases Play an Indispensable Role in the Pathogenesis of Magnaporthe oryzae - Abdul, Waheed; Aliyu, Sami R.; Lin, Lili; Sekete, Malota; Chen, Xiaomin; Otieno, Frankline J.; Yang, Tao; Lin, Yahong; Norvienyeku, Justice; Wang, Zonghua (Frontiers in Plant Science, 2018)
Oxidative degradation of lipids through lipid peroxidation processes result in the generation of free fatty acid radicals. These free radicals including reactive oxygen species (ROS) serve as a substrate for generating reactive aldehydes. Accumulation of free fatty acid radicals, ROS and reactive aldehydes in cell compartments beyond physiological threshold levels tend to exert a damaging effect on proximal membranes and distal tissues. Living organisms deploy a wide array of efficient enzymes including superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) and aldehyde dehydrogenases (ALDH) for scavenging reactive molecules and intermediates produced from membrane lipid peroxidation events. Although the contributions of SOD, CAT, and POD to the pathogenesis of microbial plant pathogens are well known, the influence of ALDH genes on the morphological and infectious development of plant pathogenic microbes is not well understood. In this study, we deployed RNA interference (RNAi) techniques and successfully silenced two putative family-four aldehyde dehydrogenase genes Potassium-activated aldehyde dehydrogenase (MoKDCDH) and Delta-1-pyrrorine-5-carboxylate dehydrogenase (MoP5CDH) in the rice blast pathogen Magnaporthe oryzae. Results obtained from phenotypic analysis of individual knock-down strains showed that RNAi mediated inactivation of MoKDCDH and MoP5CDH triggered a significant reduction in conidiogenesis and vegetative growth of ΔMokdcdh and ΔMop5cdh strains. We further observed that down-regulating the expression of MoKDCDH and MoP5CDH severely compromised the pathogenesis of the rice blast fungus. Also, the disruption of MoKDCDH and MoP5CDH M. oryzae undermined membrane integrity and rendered the mutant strains highly sensitive to membrane stress inducing osmolytes. However, the MoKDCDH and MoP5CDH knock-down strains generated in this study displayed unaltered cell wall integrity and thus suggest family-four ALDHs play a dispensable role in enforcing cell wall directed stress tolerance in M. oryzae. From these results, we deduced that family-four ALDHs play a conserved role in fostering membrane integrity in M. oryzae possibly by scavenging reactive aldehydes, fatty acid radicals, and other alcohol derivatives. The observation that down-regulating the expression activities of MoKDCDH had a lethal effect on potential mutants further underscored the need for comprehensive and holistic evaluation of the numerous ALDHs amassed by the rice blast fungus for their possible engagement as suitable targets as